2019
DOI: 10.1186/s12864-019-6356-z
|View full text |Cite
|
Sign up to set email alerts
|

JCDB: a comprehensive knowledge base for Jatropha curcas, an emerging model for woody energy plants

Abstract: BackgroundJatropha curcas is an oil-bearing plant, and has seeds with high oil content (~ 40%). Several advantages, such as easy genetic transformation and short generation duration, have led to the emergence of J. curcas as a model for woody energy plants. With the development of high-throughput sequencing, the genome of Jatropha curcas has been sequenced by different groups and a mass of transcriptome data was released. How to integrate and analyze these omics data is crucial for functional genomics research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…JcERFVII1 exhibited the highest expression in apical buds and the lowest expression in leaves, while JcERFVII2 and JcERVII3 exhibited the highest expression in roots and the lowest expression in leaves. We also compared the expression levels of the three JcERFVIIs using the transcriptome data from roots, leaves, stems, and shoot apexes collected in a publically available J. curcas database (JCDB) [ 30 ]. We found that among the three JcERFVIIs , JcERFVII1, and JcERFVII3 displayed the highest and the lowest expression, respectively ( Supplementary Materials Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…JcERFVII1 exhibited the highest expression in apical buds and the lowest expression in leaves, while JcERFVII2 and JcERVII3 exhibited the highest expression in roots and the lowest expression in leaves. We also compared the expression levels of the three JcERFVIIs using the transcriptome data from roots, leaves, stems, and shoot apexes collected in a publically available J. curcas database (JCDB) [ 30 ]. We found that among the three JcERFVIIs , JcERFVII1, and JcERFVII3 displayed the highest and the lowest expression, respectively ( Supplementary Materials Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The gene expression profiles were downloaded at April 2019 from the J. curcas database (JCDB [ 16 ], http://jcdb.liu-lab.com ) which contained 114 RNA-Seq samples. JCDB is a comprehensive database of J. curcas that we have developed in previous studies.…”
Section: Methodsmentioning
confidence: 99%
“…Given the k nearest neighbors of a gene A in a network (here we use k = 5), the naive KNN method selects the functional class that is voted for by the maximum number of neighbors, and assigns it to gene A. Gene expression data in 7 different developmental stages of J. curcas seeds was used to calculate the distance between the candidate gene and the oil-biosynthesis-related gene. Those expression data were obtained from JCDB [ 16 ] and Jiang’s paper [ 34 ]. The distance was calculated by Euclidean distance Eq.…”
Section: Methodsmentioning
confidence: 99%
“…Real-time qPCR was used to determine the copy number. The developed transgenic lines were reported to show salt tolerance up to 200 mM NaCl, which was better in comparison with the wild type [ 68 ]. The plant breeding program has significantly enhanced agricultural productivity through the development of high-yielding crop varieties.…”
Section: Genetic Transformation Studies Of Jatropha Curcas ...mentioning
confidence: 99%